Analisis penerapan psak 102 tentang akuntansi murabahah - Ariadi, Deni; Damayanti, Fitri; Setyo B, Gideon (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research is a research entitled Analysis of the Application of PSAK 102 Regarding Murabahah Accounting. This research is motivated by the growing development of financial institutions accompanied by development progress in Indonesia and in line with the increasing public need for financial institution services, especially strong and healthy Islamic financial institutions. The purpose of this is to provide an overview of how the application of PSAK 102 Regarding Murabahah Accounting at PT Bank Brisyariah Tbk in 2019, whether the recognition and measurement, presentation, and effectiveness of murabahah financing transactions have been prepared and presented in accordance with PSAK 102. run murabahah financing. The data used in this study is secondary data, data collection with documentation and literature review and data analysis in this study is descriptive qualitative. The results of this study indicate that the implementation of murabahah financing at PT Bank Brisyariah Tbk in 2019 has been prepared and presented in accordance with PSAK 102 regarding murabahah financing, but PT Bank Brisyariah Tbk in 2019 only runs murabahah by order. There are still obstacles in the application of murabahah financing, namely not knowing many third parties or suppliers in fulfilling the goods that customers want.